Conservative spine surgery: The true "minimally invasive" spine surgery/dharmendra ganesan - Dharmendra , Ganesan (University of Malaya, 2020)
"Conservative spine surgery" is a concept or perhaps a philosophy that I coined after 12 years of practicing as a consultant neurosurgeon with a subspecialized interest in spinal neurosurgery. UM deals with a plethora of patients with spinal conditions, where degenerative spinal disorder (DSD) is the one most commonly diagnosed. In managing DSD, it is imperative to understand that the symptom of pain could emanate from various anatomical structures from the spine and its surrounding structures. It is also important to appreciate the natural history of these conditions as it is equally important, to be cognizant of the immediate, short and long-term risk and been fits related to the treatment, as well as the short and long-term effects of the intervention on the inherent spine adjacent to the treatment area, which undergoes wear and tear as we age. By reflecting on the management of these cohorts of patients, I would like to discuss the importance of clinico-radiological features in identifying a clinically relevant, surgical pathology when strategizing treatment, Thence, determining the appropriate choice of "minimally invasive" surgical management, in treating that one, individual patient with the background belief that "less is more" in spine surgery. In the quest of moving with the times, we have to embrace new technology and treatment modalities, however the onus is on us surgeons to do the critical appraisal prior to practicing it and this is an area I wish to expound on. In addition to that, I will also highlight the conundrums in the application of evidence-based surgical treatment in a patient-centred management.